Towards a thermo-magneto-mechanical coupling framework for magneto-rheological elastomers. (1st December 2017) - Mehnert, Markus; Hossain, Mokarram; Steinmann, Paul
Abstract: Magnetorheological elastomers (MREs) are a relatively new class of smart materials that can undergo large deformations resulting from external magnetic excitation. These are promising candidates in producing sensors and actuators. Due to their inherent chemical compositions, most polymeric materials are highly susceptible to temperature. While performing experiments on MREs that are exposed to magneto-mechanically coupled loads, maintaining a constant temperature profile is a non-trivial task for various reasons, e.g., i) experiments need to be performed in a temperature chamber that can maintain a prescribed temperature throughout a test, and ii) additional temperature gradients can be generated internally. In this paper, a thermo-magneto-mechanically coupled constitutive model is devised that is based on the total energy approach frequently used in MREs modelling and computation. Relevant constitutive equations are derived exploiting basic laws of thermodynamics that result in a thermodynamically consistent formulation. We demonstrate the performance of the proposed thermo-magneto-mechanically coupled framework with the help of two non-homogeneous boundary value problems. In both problems an axisymmetric cylindrical tube is deformed under thermo-magneto-mechanically coupled loads. In the first example the mechanical deformation is a combination of axial stretch and radial inflation whereas in the second example the cylinder is put under a mechanical load of torsion around the cylinder axis combined with an axial stretch. In both examples a circumferential magnetic field and a radial temperature gradient are applied. The results capture various thermo-magneto-mechanical couplings with the formulation proposed for MRE.